2022
DOI: 10.1108/sbr-10-2021-0205
|View full text |Cite
|
Sign up to set email alerts
|

“Sustainable attitude” – a modest notion creating a tremendous difference in the glamourous fast fashion world: investigating moderating effects

Abstract: Purpose The purpose of this study is to examine relationship between numerous factors (fashion orientation, conspicuous consumption and environmental consciousness) that influence fast fashion (FF) purchase intention and their impact on FF purchase behavior and exploring the moderating effect of sustainable clothing consumption attitude. Design/methodology/approach This study uses quantitative analysis approach, wherein data have been collected from 571 college students by using non-probability snowball samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Fashion gives them status, improves their perception of themselves and others, and reinforces their feeling of freedom. These motivations are present in those who prefer fast fashion, slow fashion, sustainable fashion, or second-hand clothes [1,22,31,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fashion gives them status, improves their perception of themselves and others, and reinforces their feeling of freedom. These motivations are present in those who prefer fast fashion, slow fashion, sustainable fashion, or second-hand clothes [1,22,31,46].…”
Section: Discussionmentioning
confidence: 99%
“…Fashion involves "multifunctional products": garments and accessories, in addition to their practical function of covering the body and providing heat, stimulate the "hedonic value" [1] (p. 10). Since the beginning of marketing as a discipline, consumers have been sensitive and influenced by the attributes related to the illusion of an increase in social status; these factors lead them to conspicuous consumption, a behavior that may be in conflict with environmental awareness [31].…”
Section: Literature Review 21 Sustainable Fashionmentioning
confidence: 99%
“…The intersection of fast fashion and sustainable development is a critical point in the landscape of the modern fashion industry. Fast fashion, known for its rapid production cycles and trend dissemination, faces increasing scrutiny for its environmental and ethical impact [72,76,[83][84][85][86][87][88]. Acknowledging these concerns, the fashion industry is now embracing sustainable practices to address issues like overconsumption [89,90], environmental degradation [91], and carbon footprints associated with mass production.…”
Section: Cluster 3: Fast Fashion and Sustainable Developmentmentioning
confidence: 99%
“…Our study found this complex relationship, examining industry practices and perceptions to highlight challenges and opportunities for aligning fast fashion with sustainability. The transformative potential of technological innovations [92] emphasizes ethical sourcing [60,72,86,93,94], eco-friendly materials [85,95,96], and circular economy models that prioritize durability and recyclability. However, there is tension between fast CV and the growing consensus that responsible practices can coexist with the demand for rapid fashion cycles.…”
Section: Cluster 3: Fast Fashion and Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation